Evaluation of potential probiotic characteristics and antibacterial effects of strains of Pediococcus species isolated from broiler chickens. Issue 3 (3rd May 2016) - Noohi, N.; Ebrahimipour, G.; Rohani, M.; Talebi, M.; Pourshafie, M. R.
Abstract: Pediococcus spp. were isolated from poultry rectum, faeces and food as good probiotic candidates in order to select strains to be used as probiotic in poultry feed. A total of 168 lactic acid bacteria were isolated and 51 isolates including 31 Lactobacillus spp. and 20 Pediococcus spp. were able to survive in low pH and bile salt concentration. The Pediococcus spp. were identified and their ability to form biofilm, adhesion to Caco-2 cells and antimicrobial activities against enteric pathogenic bacteria were determined. The results showed the presence of two strains, Pediococcus acidilactici P17 and P19 in rectal swab samples from 21-d old chickens with significant antibacterial activities against Salmonella enteritidis and Escherichia coli . The results suggest that only a few isolates of Pediococcus with potential probiotic activities are present in the poultry industry.